Asuhan Keperawatan pada Tn. A dengan Diagnosa Medis Post Operasi Soft Tissue Tumor (STT) Flank Sinistra di Ruang Mawar 2 RSUD Dr. Soeselo Kabupaten Tegal - Adi Nur Faozan; Ahmad Zakiudin; Yusriani Saleh Baso (Vitamin : Jurnal ilmu Kesehatan Umum, 2024)
Tumor is a disease that is currently one of the health problems that causes death, soft tissue tumor or soft tissue tumor is an abnormal lump that is formed due to the growth of new cells (Irsal et al., 2020). The signs and symptoms in soft tissue tumor patients include pain due to the surgical process. The purpose of this writing is to find out and provide nursing care to Mr. A with a medical diagnosis post-operative soft tissue tumor (STT) left flank in the rose room 2 RSUD dr. Soeselo Tegal Regency in accordance with nursing standards. The methods used are descriptive methods and data collection methods. From the case review, it was found that Mr. A complains of pain. Three diagnoses were found, namely acute pain, impaired physical mobility and knowledge deficit. Interventions are prepared based on the theory of SDKI, SLKI and SIKI as well as on the client's condition and can be implemented.